Mercedes Pinto (1883-1976). Pedagogía con voz propia en el itinerario Iberoamericano (Tzintzun, Revista de Estudios Históricos, 2019)
The work we present is a semblance of the Spanish Mercedes Pinto (1883- 1976), one of the pioneers of feminism who, with her own voice, rose up in defense of the rights of women and other social causes. Avant-garde and daring woman who, in her time, was able to break with social stereotypes, standing out for her progressive thinking in the first decades of the Spanish twentieth century, which she later promoted in other latitudes, leaving an indelible trail. She toured several countries (Uruguay, Paraguay, Bolivia, Argentina, Chile, Cuba and Mexico, his last home), leaving testimonies of his thought and work.